Facilitators and barriers associated with breastfeeding among mothers attending primary healthcare facilities in Mpumalanga, South Africa - Seabela, Ethel Sekori; Modjadji, Perpetua; Mokwena, Kebogile Elizabeth (Frontiers in Nutrition, 2023)
Introduction Despite the health benefits of breastfeeding for both the mother and the child, early cessation of breastfeeding remains a public health problem in South Africa, attributed to contextual barriers and facilitators. Within the context of Mpumalanga province, which is characterized by low breastfeeding rates and high infant mortality rates in children under 5 years, we explored the facilitators and barriers to breastfeeding among mothers attending the three primary health facilities in Ermelo. Methods Using a semi-structured interview guide suggested by the socio-ecological model, three focus group discussions and 12 in-depth interviews were conducted among mothers selected using a purposive sampling. Transcripts from audiotaped and transcribed verbatim interviews were assessed through thematic analysis using NVivo version 10. Results Mothers were aged between 18 and 42 years and from poor sociodemographic backgrounds. At the individual level, mothers valued breastfeeding facilitated by their commitment, maintaining it, eating healthy foods, and having sufficient breast milk. However, returning to work, insufficient breast milk, misconceptions about breastfeeding, and interference with social life were the barriers for mothers to breastfeed continuously. At the interpersonal level, the family was identified as the main form of support to breastfeeding mothers; however, family interference was also identified as a barrier. At the community level, mothers shared some family beliefs and practices but were still split between societal and cultural norms and traditional beliefs as facilitators or barriers to breastfeeding. At the organizational level, most mothers valued the support provided by healthcare workers on childcare and techniques for breastfeeding at the health facilities. They did however articulate concerns on the miscommunication some healthcare workers offered regarding breastfeeding, which negatively influenced their infant feeding practices. Discussion Intervention efforts should focus on behaviour change to educate and equip mothers to overcome the barriers that are within their control. Such interventions should further focus on family-centered education and strengthening the proficiency of healthcare workers on advising breastfeeding mothers.